Serum Myostatin is Upregulated in Obesity and Correlates with Insulin Resistance in Humans - Amor, Melina; Itariu, Bianca K.; Moreno-Viedma, Veronica; Keindl, Magdalena; Jürets, Alexander; Prager, Gerhard; Langer, Felix; Grablowitz, Viktor; Zeyda, Maximilian; Stulnig, Thomas M. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Obesity and type 2 diabetes mellitus have reached an epidemic level, thus novel treatment concepts need to be identified. Myostatin, a myokine known for restraining skeletal muscle growth, has been associated with the development of insulin resistance and type 2 diabetes mellitus. Yet, little is known about the regulation of myostatin in human obesity and insulin resistance. We aimed to investigate the regulation of myostatin in obesity and uncover potential associations between myostatin, metabolic markers and insulin resistance/sensitivity indices. Circulating active myostatin concentration was measured in the serum of twenty-eight severely obese non-diabetic patients compared to a sex and age matched lean and overweight control group (n=22). Insulin resistance/sensitivity was assessed in the obese group. Skeletal muscle and adipose tissue specimens from the obese group were collected during elective bariatric surgery. Adipose tissue samples from lean and overweight subjects were collected during elective abdominal surgery. Myostatin concentration was increased in obese compared to lean individuals, while myostatin adipose tissue expression did not differ. Muscle myostatin gene expression strongly correlated with expression of metabolic genes such as IRS1, PGC1α, SREBF1. Circulating myostatin concentration correlated positively with insulin resistance indices and negatively with insulin sensitivity indices. The best correlation was obtained for the oral glucose insulin sensitivity index. Our results point to an interesting correlation between myostatin and insulin resistance/sensitivity in humans, and emphasize its need for further evaluation as a pharmacological target in the prevention and treatment of obesity-associated metabolic complications.
Keywords: obesity; type 2 diabetes mellitus; insulin resistance/sensitivity indices